2020
DOI: 10.3390/en14010163
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Electrical Output and Reliability Characteristics of the Crystalline Photovoltaic Module According to the Front Materials

Abstract: In recent years, various types of installations such as floating photovoltaic (PV) and agri-voltaic systems, and BIPV (building integrated photovoltaic system) have been implemented in PV systems and, accordingly, there is a growing demand for new PV designs and materials. In particular, in order to install a PV module in a building, it is important to reduce the weight of the module. The PV module in which low-iron, tempered glass is applied to the front surface, which is generally used, has excellent electri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…The yellowing effect of PC after UV aging test has also been observed by Redjala, S., et al [25], whereas ETFE showed no discoloration, as could be seen through the naked eye. This similar observation was also noticed by another research group [26].…”
Section: Uv Test Analysis Of Lightweight Front Materialssupporting
confidence: 90%
See 1 more Smart Citation
“…The yellowing effect of PC after UV aging test has also been observed by Redjala, S., et al [25], whereas ETFE showed no discoloration, as could be seen through the naked eye. This similar observation was also noticed by another research group [26].…”
Section: Uv Test Analysis Of Lightweight Front Materialssupporting
confidence: 90%
“…Another study showed a decrease in transmittance in PMMA of about 5% after UV exposure of 360 h [28]. The negligible decrease in transmittance of ETFE after UV exposure was already seen [26]. This shows that ETFE has superior UV characteristics as compared with other materials.…”
Section: Uv Test Analysis Of Lightweight Front Materialsmentioning
confidence: 94%
“…A failure is a state in which a system fails to realize its expected function. The failure analysis of a PV installation requires the creation of a model of the installation [12]. A photovoltaic power plant usually consists of photovoltaic panels, an inverter, and the electronics and power electronics that control the plant [13].…”
Section: Operation and Failures Of Photovoltaic Installationsmentioning
confidence: 99%
“…At the same time, solar radiation can also be converted to electricity using solar power systems. Solar systems are classified into two types: photovoltaic (PV) systems that convert sunlight directly to electricity using semiconductor materials [36,[76][77][78][79] and concentrated solar power (CSP) systems that convert sunlight to heat before using the heat to produce electricity [30,41,46,51,80]. Despite the fact that both processes need solar radiation to occur, the photosynthesis process is concerned more with the Photosynthesis Active Radiation (PAR) range [47,52,68,[81][82][83] while electrical energy generation is dependent on solar irradiance or light intensity [8,15,35,84,85].…”
Section: The Importance Of Solar Radiation For Energy Generation and Crop Cultivationmentioning
confidence: 99%
“…These two systems are intended to offer a direct current or alternating current source for use with the utility grid, an independent storage system, or other electrical/electronic equipment [77,93,119,120]. Even though much of the photovoltaic system demand can be matched with aggressive building-integrated PV (BIPV) and rooftop PV [79,87,95,102], both systems cannot provide all the energy necessary, especially for regions with high population densities compared to land-based solar farms [8,95]. A solar farm is designed to generate enough energy [37] to power thousands of homes and business [9,121].…”
Section: Alteration and Modification Of Solar Photovoltaicmentioning
confidence: 99%